Analysis of Consumer Behavior on the Decision to Pay Electricity Account Arrears at PT PLN (PERSERO) UID North Sumatra - Bunga Widuri Marina; Nurafrina Siregar (International Journal of Management, Economic and Accounting, 2024)
This study aims to analyze consumer behavior in making decisions to pay electricity account arrears at PT PLN (Persero) UID North Sumatra. With the increasing number of electricity account arrears, it is important to understand the factors that affect consumer behavior in making payments. The research method used is a quantitative approach with a survey of customers who have arrears. Data was collected through questionnaires that included variables such as awareness of payment obligations, level of understanding of bills, as well as external motivational factors such as fines and service termination. The results of the analysis show that consumer awareness and understanding of bills have a significant influence on the decision to pay arrears. In addition, external motivation factors also play a role in encouraging consumers to settle arrears. This study provides recommendations for PT PLN to increase socialization regarding payment obligations and offer more flexible solutions for consumers in resolving their arrears.